2019
DOI: 10.3390/ijerph16101725
|View full text |Cite
|
Sign up to set email alerts
|

Combining Heart Rate Variability with Disease Severity Score Variables for Mortality Risk Stratification in Septic Patients Presenting at the Emergency Department

Abstract: The emergency department (ED) serves as the first point of hospital contact for many septic patients, where risk-stratification would be invaluable. We devised a combination model incorporating demographic, clinical, and heart rate variability (HRV) parameters, alongside individual variables of the Sequential Organ Failure Assessment (SOFA), Acute Physiology and Chronic Health Evaluation II (APACHE II), and Mortality in Emergency Department Sepsis (MEDS) scores for mortality risk-stratification. ED patients fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In addition, when we restricted analysis to studies (19-24, 26, 28, 31, 32, 34-38) that evaluated the NEWS at admission or excluded five studies with small sample sizes (20,24,27,31,32), the sensitivity analyses showed similar results to the primary result.…”
Section: Subgroup and Sensitivity Analysesmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, when we restricted analysis to studies (19-24, 26, 28, 31, 32, 34-38) that evaluated the NEWS at admission or excluded five studies with small sample sizes (20,24,27,31,32), the sensitivity analyses showed similar results to the primary result.…”
Section: Subgroup and Sensitivity Analysesmentioning
confidence: 90%
“…These studies recruited a total of 107,008 participants, and the mortality rate in each study ranged from 2.5 to 32.8%. Five studies (20,24,27,31,32) were relatively small in sample size (<400), and 10 studies (19, 23, 26, 28-30, 33, 36, 37, 40) enrolled more than 1,000 patients. Ten studies (19,21,22,(27)(28)(29)(32)(33)(34)(35) included patients with suspected infection, and others focused on patients with suspected sepsis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The HRV-based classifier could identify hypertensive patients at high risk of developing vascular events with high sensitivity and specificity (71.4 and 87.8%, respectively) (51). A combination model incorporating HRV and other disease severity score variables showed optimal predictive ability of 30-day in-hospital mortality for septic patients at the emergency department against conventional risk stratification tools (AUC = 0.91, 95% confidence interval: 0.88-0.95) (52,53). The exploitation of HRV in risk stratification tools of stroke becomes one of the vital and prophylactic measures for high-risk individuals to ring alarm bells.…”
Section: Use Of Hrv For Stratifying the Risk Of Strokementioning
confidence: 99%
“…Being a non-invasive tool that can be rapidly obtained even from patients who are unable to give a history, HRV has been shown to be dysregulated in sepsis [ 13 ] and correlates well with subsequent mortality [ 14 , 15 ]. Indeed, scoring systems that incorporate HRV parameters among its predictors have outperformed traditional clinical indicators and established disease severity scores in predicting sepsis mortality [ 16 19 ]. The use of HRV may thus further enhance our ability to stratify for risk of sepsis mortality.…”
Section: Introductionmentioning
confidence: 99%